AVALIAÇÃO DA INCORPORAÇÃO DE CLOREXIDINA EM SISTEMAS ADESIVOS NA LIBERAÇÃO E SEUS EFEITOS NA LONGEVIDADE DA INTERFACE DE UNIÃO À DENTINA - Malaquias, Pamela (2016)
The aim of the study was to evaluate the effects of adding chlorhexidine diacetate (CHX), in two different simplified adhesive systems on the chlorhexidine release (CHXR), bond strength (μTBS) and nanoleakage (NL). The CHX was added to adhesive systems XP Bond [XP] (Dentsply, York, PA, USA) and Ambar [AM] (Prod Odont Ltda FGM, Joinville, Brazil) at concentrations of 0 (control); 0.01; 0.05; 0.1 to 0.2% wt. To assess the cumulative CHXR, adhesives disks (n = 10 for each group) were prepared in a metallic matrix (5.8 mm x 1.0 mm) and stored in distilled water. Spectrophotometric measurements of the storage solution were performed to examine the kinetics of release of CHX. For μTBS and NL 50 extracted third molars were used and they had a flat surface of dentin exposed, and were randomly divided according to the different experimental groups mentioned above. This was followed by clinical sequence specified by the manufacturer of each adhesive system. After applying the adhesive, resin composite restorations was built in layers. Then, the specimens were prepared and subjected to microtensile and nanoleakage testing at 24 and 24 months of storage in water at 37°C. For CHXR (% and mg/g), the data of each adhesive were subjected to a two-way ANOVA. The μTBS data (MPa) and NL (%) of each adhesive were submitted to analysis of variance of two factors (ANOVA). The Tukey test was used for pairwise comparisons (α = 0.05). Regarding CHXR, Ambar showed a slower and gradual release of CHX while XP Bond released CHX more quickly. In μTBS, Ambar showed better values in percentage of bond strength reduction after 2 years of storage in water. Both adhesives showed better bond strength values in groups containing CHX compared to the control group (without CHX). In NL, the control group had a higher nanoleakage in 2 years. XP had a higher nanoleakage that Ambar in all groups. We concluded that the addition of CHX diacetate until 0.2% is a viable method of providing a long-term increase in the stability of resin-dentin interfaces without compromising the properties of the adhesives systems.